LED-Lamp Design for Renewable Energy-Based DC House Application - Rini Nur Hasanah; Yosi Dwi Handari; Soeprapto Soeprapto; Taufik Taufik (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper describes the design of an LED lamp to be used in a DC house being supplied using a renewable energy source or in a DC Smart Grid. LED lamps are widely known for its low-electricity consumption. The DC house application is becoming more and more popular due to its advantage of using DC generated electricity, for example from a solar photovoltaic system, directly without having to invert it into AC voltage. However, LED needs a driver to activate and control it. Its mounting also needs certain precaution to anticipate the high heat from the LED. An appropriate heatsink is required before activating the LED. The laboratory results indicate that a 3-watt LED bulb lamp can produce an efficiency up to 93.16% with luminous efficacy 82.29 lm/W. These results prove that an LED bulb consumes less energy and can give an optimal brightness.